2015
DOI: 10.1021/acsami.5b00631
|View full text |Cite
|
Sign up to set email alerts
|

Glucose- and pH-Responsive Nanogated Ensemble Based on Polymeric Network Capped Mesoporous Silica

Abstract: In this paper, a glucose and pH-responsive release system based on polymeric network capped mesoporous silica nanoparticles (MSN) has been presented. The poly(acrylic acid) (PAA) brush on MSN was obtained through the surface-initiated atom transfer radical polymerization (SI-ATRP) of t-butyl acrylate and the subsequent hydrolysis of the ester bond. Then the PAA was glycosylated with glucosamine to obtain P(AA-AGA). To block the pore of silica, the P(AA-AGA) chains were cross-linked through the formation of bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 40 publications
0
49
0
Order By: Relevance
“…The pH-sensitive linkers, such as acetal bond, [65][66][67] hydrazine bond, [68][69][70][71] hydrazone bond, 72 and ester bond, 73,74 can be cleaved under acidic condition, thus providing opportunities for designing pH-responsive DDS applied in cancer treatment. Liu et al 65 reported a new pH-responsive nanocarrier by capping gold nanoparticles onto the surface of mesoporous silica through acid-labile acetal linkers ( Figure 3).…”
Section: Song Et Almentioning
confidence: 99%
“…The pH-sensitive linkers, such as acetal bond, [65][66][67] hydrazine bond, [68][69][70][71] hydrazone bond, 72 and ester bond, 73,74 can be cleaved under acidic condition, thus providing opportunities for designing pH-responsive DDS applied in cancer treatment. Liu et al 65 reported a new pH-responsive nanocarrier by capping gold nanoparticles onto the surface of mesoporous silica through acid-labile acetal linkers ( Figure 3).…”
Section: Song Et Almentioning
confidence: 99%
“…External stimuli such as temperature, [7][8][9][10][11][12][13]15 pH, 16,17 stress, 18 ions, 19 solvents, 20 ligands, 21 and biomaterials cause a color change to the red phase with l max around 550 nm. 22 The intriguing stimuli-responsive color change properties [23][24][25] show potential for applications in sensing.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Inorganic nanoparticles, especially mesoporous silica nanoparticles (MSNs), have been considered as one class of potential DDS owing to their chemical stability, tunable microstructures, large surface area, high biocompatibility, and the ease of functionalization. [2] Recent studies confirmed that nanoparticles such as MSNs may present other profoundly powerful cellular effects. Their interaction with cells may result in the formation of a gap, facilitating the particles to pass cross endothelial barrier to reach the cells.…”
Section: Introductionmentioning
confidence: 99%